The dark net : inside the digital underworld - Bartlett, Jamie (Tantor Audio, 2017)
Beyond the familiar online world that most of us inhabit lies a vast and often hidden network of sites, communities, and cultures where freedom is pushed to its limits, and where people can be anyone, or do anything, they want. This is the world of Bitcoin and Silk Road, of radicalism and pornography. This is the Dark Net.